Eco-Revelatory Urban Design: Towards a Conceptual Framework - Aida Esmailzadeh Seilabi; Kourosh Golkar; S Hassan Taghvaei; Marjan Nematimehr (صفه)
Neglecting cities’ natural environment in urban development has led to intentional or inadvertent loss of several ecosystem services in Iran. Consequently, this has directly affected the overall urban quality of life, citizens’ cognitive experience, and their value systems. Approaches to solve this problem include Landscape Urbanism, Urban Ecological Restoration, and Eco-Revelatory Urban Design. The latter approach aims at highlighting the ecological qualities of urban natural environment and improving its ecosystem services. Employing an analysis-descriptive methodology, this paper attempts to elaborate a conceptual framework for measuring the eco-revelatory dimension of urban environment as an essential quality of urban design.